The fierceness of fronted /s/: Linguistic rhematization through visual transformation - Calder, Jeremy (Language in Society, 2019)
This article explores the roles that language and the body play in the iconization of cross-modal personae (see Agha 2003, 2004). Focusing on a community of radical drag queens in San Francisco, I analyze the interplay of visual presentation and acoustic dimensions of /s/ in the construction of the fierce queen persona, which embodies an extreme, larger-than-life, and anti-normative type of femininity. Taking data from transformations—conversations during which queens visually transform from male-presenting into their feminine drag personae—I explore the effect of fluid visual presentation on linguistic production, and argue that changes in both the linguistic and visual streams increasingly invoke qualia (see Gal 2013; Harkness 2015) projecting ‘harshness’ and ‘sharpness’ in the construction of fierce femininity. I argue that personae like the fierce queen become iconized through rhematization (see Gal 2013), a process in which qualic congruences are construed and constructed across multiple semiotic modalities. (Iconization, rhematization, qualia, sociophonetics, gender, personae, drag queens)*
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; drag queen; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; san francisco; sciences humaines; thématiques; états-unis

Langage, genre et sexualité - Auger, Nathalie (Collection Langue et pratiques discursives, 2011)
L'objectif de cet ouvrage est d'examiner les liens complexes entre langage, genre et sexualité. En adoptant un positionnement résolument critique, qui met l'accent sur les aspects historique, politique et social des pratiques langagières, cet ouvrage part de l'idée que le genre et l'identité sexuelle sont avant tout des constructions sociales et idéologiques qui trouvent une forme de matérialité, entre autres, dans les discours et les pratiques sociales. Nous croyons que ces processus langagiers participent à la formation des différences et des inégalités - sans toutefois en être l'unique cause -, qu'ils contribuent à la réification des catégories au même titre qu'ils permettent d'en créer de nouvelles.--Résumé de l'éditeur.
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; europe; france; francophonie; féminisme matérialiste; identités LGBTQIA2+; langue; lin2685; linguistique; premier cycle; queer; québec; régions géographiques; sciences humaines; sexualité; sociolinguistique; thématiques